Influência dos teores de água e impurezas na qualidade de grãos de arroz submetidos à secagem estacionária - Nunes, Marcela Trojahn (2021)
Rice (Oryza sativa) is one of the main foods of the world population, having starch as the main nutrient. Drying is considered one of the most important steps in grain processing, which aims to reduce the water content to levels that allow for safe preservation and stability. However, grain composition and quality may change due to inadequate drying management. The storage silo with air flow for drying has the advantage of being able to store and dry the product at the same time, but there is unevenness in the distribution of the drying air, especially when there is an excess of impurities, impairing the quality of the grains. The research aims to evaluate the performance of drying air movement in the mass of rice grains stored in storage silos with air flow for drying as a function of water and impurity content variation. The research was carried out in a storage complex, carrying out three experiments, analysis of movement in the grain column, quality of rice grains stored with different water and impurities contents and air movement through different cleaning operations of grinding in the grain mass. To analyze the quality of the grains at different points of the storage silo with air flow for drying, the principle of a completely randomized, factorial (4x11) design was used, with three sampling repetitions, followed by Tukey test at 5% probability, using different techniques, Near Infrared Spectroscopy (NIR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM), to verify the physicochemical quality of rice. All silos showed a low drying performance. When observing the air flow during silo loading, a reduction in air flow and specific air flow was identified, while there was an increase in static pressure. In silos where there was no complete grinding cleaning process, there was an increase in static pressure, with greater air output at specific points, interfering with air distribution and drying. When analyzing the influence of the water content and impurity ratio of the stored grains, the 19U/1.5I ratio revealed a higher yield, as well as a lower amount of grains with defects, broken and plastered. It was also possible to identify that the lower layer of the storage silo with air flow for drying in the 19U/1.5I, 18U/2.0I and 17U/2.5I treatments had the physical quality of the grains impaired, due to the high temperature, as a result the formation of a drying front. When analyzing rice grains with high starch content by SEM, it was found that they have a greater tendency to form roughness in their structure. However, the starch content was not directly related to the crystallinity index. Allowing to identify that the inadequate management of the storage silo with air flow for drying interferes with the drying of the grains and that the lack of care prior to storage can harm the final quality of the product, since the system has technical limitations in the movement of drying air.